Intersex or Diverse Sex Development: Critical Review of Psychosocial Health Care Research and Indications for Practice. Issue 4 (13th June 2019) - Roen, Katrina
Abstract : Intersex or diverse sex development (dsd) can be conceptualized as an aspect of bodily diversity that has particular psychosocial implications. This is a review of psychosocial health care literature, published from 2007 to 2017, focusing on the well-being of people with a diagnosis relating to sex development. The analysis I offer here takes a critical psychological approach, questioning norms and taken-for-granted assumptions. This approach works from the understanding that how we know and how we talk about a phenomenon affects people in material and life-changing ways. This article offers recommendations concerning health care communication, the importance of taking time for emotion, and the process of building supportive relationships. The research reviewed provides clear evidence of psychosocial harm that is done through genital intervention and evidence that parents do not routinely give fully informed consent before their children undergo treatment. Finally, I highlight key points and recommendations for health professionals, indicating how psychosocial professionals can contribute to health care and well-being in the context of dsd when appropriately resourced and trained.